2020
DOI: 10.1002/jcla.23433
|View full text |Cite
|
Sign up to set email alerts
|

CircHN1 affects cell proliferation and migration in gastric cancer

Abstract: Background Increasing evidence indicates that circular RNAs (circRNAs) are dysregulated in human cancers. The biological roles of circRNAs in gastric cancer (GC) have not been well‐characterized. Methods The GEO database was used to analyze circRNA expression profile in GC. The expression level of target circRNA in tumor tissues and adjacent non‐tumor tissues was detected by reverse transcription‐quantitative PCR. Gene transfection was used to manipulate the expression of circRNAs. The biological roles of circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“… 27 However, Zhang et al reported that miR-1248 functioned a tumor suppressor in gastric cancer. 28 Therefore, miR-1248 might have different roles in different cancers. However, it was worth noting that miR-1248 also was significantly low in NSCLC, 29 and our findings were consistent with it.…”
Section: Discussionmentioning
confidence: 99%
“… 27 However, Zhang et al reported that miR-1248 functioned a tumor suppressor in gastric cancer. 28 Therefore, miR-1248 might have different roles in different cancers. However, it was worth noting that miR-1248 also was significantly low in NSCLC, 29 and our findings were consistent with it.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that circRNAs containing miRNA response elements (MREs) can work as miRNA sponges 14,15 . For example, CiRS‐7 containing 74 miR‐7 binding sites can act as a miR‐7 sponge with high miRNA‐binding capacity and can participate in post‐transcriptional regulation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that circRNAs containing miRNA response elements (MREs) can work as miRNA sponges. 14,15 For example, CiRS-7 containing 74 miR-7 binding sites can act as a miR-7 sponge with high miRNA-binding capacity and can participate in posttranscriptional regulation. 5 MiR-7 plays a key role in Parkinson's disease, which indicates the potential role of CiRS-7 in the progression of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Similarly, circHN1, circMAN2B2, and hsa_circ_0023642 were also found to affect the growth and migration of GC cells by the similar ways. 16 , 17 , 18 All these circRNAs can serve as potential biomarkers and targets for the diagnosis and therapy of GC, which strongly suggests an important role of altered circRNAs in cancer pathophysiology.…”
Section: Discussionmentioning
confidence: 99%